Analysis of re-infection cases and influencing factors post first severe COVID-19 wave in Jiangsu Province, China - Qigang Dai; Changjun Bao; Hao Ju; Na Li; Shizhi Wang; Jiaxin Wen; Qiang Zhou; Liling Chen; Yujun Chen; Lei Xu; Xin Zhou; Songning Ding; et al. (Journal of Infection in Developing Countries)
Introduction: This study aimed to assess COVID-19 re-infection rates among individuals previously infected between 2020 and November 2022, particularly during the first wave of high-intensity transmission, and to identify the risk factors associated with re-infection in Jiangsu Province, China.